Exploring the digital frontier - Woodsworth, Anne (Advances in librarianship,, 2010)
"This volume presents international research and exhaustive reviews of literature on a range of issues related to the evolving digital environment. Topics addressed include the educational impact of the digital environment on LIS education curricula and delivery mechanisms, and information representation and learning in videogames. Issues surrounding the improvement of library catalogues by emulating Web based search engines, and the extent to which collaborative information seeking is/is not enabled by existing search engines and tools are explored. This volume also presents research on social semantic corporate digital libraries, the use of E-texts in research projects in the humanities, and information access in e-government environments. With the growing trend for digital-only access to information, this volume of Advances in Librarianship makes an important contribution in both highlighting problems and challenges, and pointing to pathways for future solutions. The Advances in Librarianship book series covers current research and professional issues in libraries, the information industry, education and development of information professionals. The series is a key resource for practitioners, researchers, students and faculty members seeking in-depth literature and solutions to current and emerging issues in library and information science and related fields."